EFFICIENCY ANALYSIS OF PARALLEL ROUTINE USING PROCESSOR TIME VISUALIZATION - Turchenko, Volodymyr; Demchuk, Viktor (International Journal of Computing, 2014)
The coarse-grain parallel algorithm of modular neural networks training with dynamic mapping onto processors of parallel computer is described in this paper. Parallelization of the algorithm is done on parallel computer 300 using MPI technology. The efficiency of this algorithm is estimated using modification of MPE visualization library, which measures processor executing time of parallel routines.